If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x = 0
x = 0
x = 0
x in (-oo:0) U (0:+oo)
2*x-3 = 1/x // - 1/x
2*x-(1/x)-3 = 0
2*x-x^-1-3 = 0
2*x^1-1*x^-1-3*x^0 = 0
(2*x^2-3*x^1-1*x^0)/(x^1) = 0 // * x^2
x^1*(2*x^2-3*x^1-1*x^0) = 0
x^1
2*x^2-3*x-1 = 0
2*x^2-3*x-1 = 0
DELTA = (-3)^2-(-1*2*4)
DELTA = 17
DELTA > 0
x = (17^(1/2)+3)/(2*2) or x = (3-17^(1/2))/(2*2)
x = (17^(1/2)+3)/4 or x = (3-17^(1/2))/4
x in { (3-17^(1/2))/4, (17^(1/2)+3)/4}
x in { (3-17^(1/2))/4, (17^(1/2)+3)/4 }
| 23-x=3x+51 | | 4/7=20/m | | 8+15g=15+8 | | 4x^2-16x=20 | | 6+2n=1+3n | | 8+15g= | | 1=2sin(2x) | | 6/d=12/17 | | 16x^2-30x+9=0 | | 1-7/25 | | -6(7x-1)=-8x+9(-3-4) | | -8-7(1+8x)=-x+40 | | 0.3x-6-x=-4.6 | | 3ax(3ax)+abx-3bx-b(b)=0 | | -4n+1=9-2x | | 8(2x+1)=55 | | 6/b=66 | | x+x(.1)=140000 | | 7x-7+3x=6x-1 | | -2/9x=4 | | 6x+9=5x-3 | | 9-4n=5-2n | | -6(7x-1)=-8+9(-3x-4) | | x^2+4xy+4y^2-3x=6 | | 10x-9y=66 | | -7x-2=-8x-8 | | 5x+y=20(1) | | 6-6x=5-5x | | -7x^2+bx-5=0 | | 6q+2+3q+2= | | 3-5x=7x+159 | | D/11-6=1 |